Language Diversity in Mathematics Teacher Education: Challenges Across Three Countries - Essien, Anthony A.; Chitera, Nancy; Planas, Núria (Mathematics Education and Language Diversity, 2015)
This chapter focuses on the awareness and the practices of mathematics teacher educators in linguistically diverse classrooms across three countries—South Africa, Malawi, and Catalonia-Spain. We explore whether and how mathematics teacher educators’ awareness in three mathematics classrooms (one from each country) impact on classroom practice and whether these practices were anchored in becoming teachers of mathematics, becoming teachers of mathematics in multilingual classrooms, becoming learners of mathematics content or becoming proficient English users. The findings reveal that the mathematics teacher educators were generally aware of the context of their practice: that they were teaching linguistically diverse mathematics student teachers who would most likely teach mathematics in a similar linguistic context. However, the practices that were used by these teacher educators were anchored in and position mathematics student teachers as becoming teachers of mathematics and becoming learners of mathematics content. Little attention was paid to becoming teachers of mathematics in multilingual contexts.